ELTD1 deletion reduces vascular abnormality and improves T-cell recruitment after PD-1 blockade in glioma. Issue 3 (4th August 2021) - Huang, Hua; Georganaki, Maria; Conze, Lei Liu; Laviña, Bàrbara; van Hooren, Luuk; Vemuri, Kalyani; van de Walle, Tiarne; Ramachandran, Mohanraj; Zhang, Lei; Pontén, Fredrik; Bergqvist, Michael; Smits, Anja; et al.
Abstract: Background: Tumor vessels in glioma are molecularly and functionally abnormal, contributing to treatment resistance. Proteins differentially expressed in glioma vessels can change vessel phenotype and be targeted for therapy. ELTD1 (Adgrl4) is an orphan member of the adhesion G-protein-coupled receptor family upregulated in glioma vessels and has been suggested as a potential therapeutic target. However, the role of ELTD1 in regulating vessel function in glioblastoma is poorly understood. Methods: ELTD1 expression in human gliomas and its association with patient survival was determined using tissue microarrays and public databases. The role of ELTD1 in regulating tumor vessel phenotype was analyzed using orthotopic glioma models and ELTD1 −/− mice. Endothelial cells isolated from murine gliomas were transcriptionally profiled to determine differentially expressed genes and pathways. The consequence of ELTD1 deletion on glioma immunity was determined by treating tumor-bearing mice with PD-1-blocking antibodies. Results: ELTD1 levels were upregulated in human glioma vessels, increased with tumor malignancy, and were associated with poor patient survival. Progression of orthotopic gliomas was not affected by ELTD1 deletion, however, tumor vascular function was improved in ELTD1 −/− mice. Bioinformatic analysis of differentially expressed genes indicated increased inflammatory response and decreased proliferation in tumor endothelium in ELTD1 −/− mice. Consistent with an enhanced inflammatory response, ELTD1 deletion improved T-cell infiltration in GL261-bearing mice after PD-1 checkpoint blockade. Conclusion: Our data demonstrate that ELTD1 participates in inducing vascular dysfunction in glioma, and suggest that targeting of ELTD1 may normalize the vessels and improve the response to immunotherapy.